A new thylacosmilid (Mammalia, Metatheria, Sparassodonta) from the Miocene of Patagonia, Argentina - Forasiepi, Analía M.; Carlini, Alfredo A. (Zootaxa, 2010)
A new genus and species, Patagosmilus goini, of the family Thylacosmilidae (Mammalia, Metatheria, Sparassodonta) is described here. The new taxon is based on a single specimen collected from the west margin of the Río Chico, in Río Negro Province, Argentina, from the middle Miocene Colloncuran SALMA. Until now, two formally recognized species were encompassed in the family Thylacosmilidae: Thylacosmilus atrox, from the late Miocene-late Pliocene Huayquerian to Chapadmalalan SALMAof Argentina and probably Uruguay; and Anachlysictis gracilis, from the middle Miocene Laventan SALMA of Colombia. Recognition of the Patagonian taxon, Patagosmilus, provides new anatomical data, likely to be included in future phylogenetic analyses. The overall morphology of Patagosmilus suggests that it has a more generalized anatomy than Thylacosmilus. The dental morphology suggests the new Patagonian taxon was probably closer to Thylacosmilus than Anachlysictis. Saber-tooth thylacosmilids have several autapomorphic features in the skull that differentiate them from other sparassodonts, including the delayed replacement or non-replacement of the deciduous last premolar.